INNOVATIVENESS OF TRAINING COMPANIES IN THE WEST POMERANIAN VOIVODESHIP - Smolska, Małgorzata (Management and Administration Journal, 2024)
The aim of the article is to analyse and evaluate the innovativeness of training companies operating in the West Pomeranian Voivodeship. In the theoretical part of the article: the basic concepts related to the innovativeness of training companies are defined and the indicators for measuring the innovativeness of these enterprises are summarised. The practical part of the article analyses the innovativeness of training companies in the West Pomeranian Voivo-deship. The following research methods were used in the article: literature analysis, analysis of source data from the Central Statistical Office, analysis of primary data obtained as a result of quantitative research.